PEMANFAATAN KARTU HURUF DALAM MENINGKATKAN KEMAMPUAN MEMBACA DI KELAS 2 SDK JOGE - Efrida ita; Maria Yasinta Fono, Maria Natalia Defatima Tai (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research aims to improve students' reading skills through the use of letter cards at SDK Joge. This type of research uses a qualitative descriptive type with data collection methods in the form of observation, documentation interviews. The subjects in this research were all students at SDK Joge. The results of this research show that learning activities using letter cards for grade 2 students at SDK Joge have increased. This can be seen from the results of observations that there are several students who have difficulty reading. Reading difficulties in grade 2 students are caused by students who cannot yet distinguish letters of the alphabet, for example "F", "V". Apart from that, students are not yet able to read letters well and students are still unsure about pronouncing or pronouncing the letters designated by the teacher. Based on this problem, researchers used letter cards to improve students' reading skills  at  SDK  Joge  with  assessment  aspects  in  the  form  of  arranging  A-Z  letter cards,recognizing and pronouncing or pronouncing letters correctly, arranging letter cards into words and spelling words. After carrying out learning activities using letter cards, there was an increase, namely from 16 students in class 2, initially there were 5 students who were able to read, now after learning using cards, there has been an increase to 14 students who can read well, and 2 students still need teacher assistance